A Review of Biomechanical and Physiological Effects of Using Poles in Sports - Maximilian Saller; Niko Nagengast; Michael Frisch; Franz Konstantin Fuss (Bioengineering, 2023)
The use of poles in sports, to support propulsion, is an integral and inherent component of some sports disciplines such as skiing (cross-country and roller), Nordic walking, and trail running. The aim of this review is to summarize the current state-of-the-art of literature on multiple influencing factors of poles in terms of biomechanical and physiological effects. We evaluated publications in the subfields of biomechanics, physiology, coordination, and pole properties. Plantar pressure and ground reaction forces decreased with the use of poles in all included studies. The upper body and trunk muscles were more active. The lower body muscles were either less active or no different from walking without poles. The use of poles led to a higher oxygen consumption (VO2) without increasing the level of perceived exertion (RPE). Furthermore, the heart rate (HR) tended to be higher. Longer poles reduced the VO2 and provided a longer thrust phase and greater propulsive impulse. The mass of the poles showed no major influence on VO2, RPE, or HR. Solely the activity of the biceps brachii increased with the pole mass.